Síntese de zeólitas tipo ton utilizando um sal de imidazólio como agente direcionador de estrutura - Lopes, Christian Wittee (2014)
This work reports the synthesis of zeolites with different compositions (pure silica, Si/Ti and Si/Al), via hydroxide and fluoride medium using the cation 1-butyl-3- methylimidazolium as structure directing agent. Initially, the cation was synthesized in chloride form and used for the synthesis in hydroxide medium. An anion-exchange (Cl- for OH-) was required for the synthesis in fluoride medium. Different reactants were used for the formation of gels synthesis, resulting in the crystallization of MFI and TON phases, the latter predominant in many compositions. The cation and synthesized zeolites obtained were characterized by different techniques such as NMR, TG/DTG, XRD, SEM, N2 adsorption and desorption, DRS and EPMA. Besides characterizing the cation and zeolites, the mother liquor of hydroxide synthesis was characterized and it was possible to observe a modification of the cation in the synthesis conditions employed. The materials synthesized in this work can be applied in catalytic reactions and adsorption